Sequência didática de educação financeira: uma investigação da mobilização da argumentação em matemática - Freitas, Nadir Santos (2023)
The teaching of financial education has featured prominently in Brazil, especially after the notes of the Organization for Economic Cooperation and Development, and the elaboration of the National Strategy for the Development of Education, culminating in the incorporation of the theme in basic education from the National Base Common Curriculum. On the other hand, we can point to a rejection of mathematics teaching based only on technical knowledge, unrelated to the reality of individuals. It is in this context, starting from a look at Critical Mathematics Education, that this work has as its main objective to identify evidence of how a didactic sequence in school financial education for high school can be used as a didactic instrument to mobilize students' arguments. Therefore, we sought to: a) Elaborate and Develop a didactic sequence based on the assumptions of the Theory of Didactic Situations (TSD) involving school financial education for high school in a perspective of critical mathematics education to mobilize students' argumentation; b) Check if there was mobilization of the students' argumentation from the development of the elaborated didactic sequence. The theoretical contributions for the research were based on Brousseau, with the Theory of Didactic Situations, Skovsmose, in relation to Critical Mathematics Education, Toulmin, in relation to the model of analysis of the argumentation and Silva and Powell, in relation to the teaching of financial education in schools. The research can be considered of a qualitative nature, with documentary, exploratory and descriptive aspects and had the participation of students from a high school class in the integral teaching modality of a state school in Alagoas. We tried to identify constituent elements of the arguments constructed by the students from the application of a didactic sequence elaborated by us; before (through data collection in focus groups) and after (through a questionnaire called “exploratory activity”), and for the analysis of these elements, we used Toulmin's model. With regard to the constructed results of the steps that make up the didactic sequence, they were evaluated using the Content Analysis technique, according to Moraes. As a result, we noticed that the arguments presented after the SD, had a significant improvement, where about 47% of the students were able to articulate the data, presenting the guarantees and support, reaching the conclusion. In this way, the didactic sequence is understood taking into account the theoretical framework of the Theory of Didactic Situations, linking mathematics contents to different areas of knowledge with a focus on addressing the social, economic and political spheres; in addition, the didactic sequence is configured as a pedagogical tool capable of enabling the mobilization of argumentation in mathematics learning.